Individual variability in the stress response of C57BL/6J male mice correlates with trait anxiety - Mira Jakovcevski; Melitta Schachner; Fabio Morellini (2007)
Stress strongly alters the physiology and behavior of some individuals, while others are little or not affected. The causes of this individual variability have remained unknown. Here, we hypothesize that epigenetically induced levels of trait anxiety predict the stress response of individual mice in a genetically homogeneous population. Inbred C57BL/6 male mice were selected for their latency to freely enter from their home cage into an unfamiliar arena and classified as having high or low levels of trait anxiety. Mice were then exposed to acute stress (1-h olfactory contact with a rat) or control conditions. After 24 h, acute stress enhanced state anxiety measured in the elevated-plus maze test only in mice previously classified as having high levels of trait anxiety. This anxiogenic effect of acute stress was paralleled by enhanced novelty-induced plasma corticosterone secretion and increased messenger RNA (mRNA) expression for glucocorticoid and mineralocorticoid receptors in the hippocampus. No effects of acute stress were observed in mice classified as having low levels of trait anxiety. Under unstressed control conditions, mice only differed in basal levels of hippocampal mRNA for the glucocorticoid receptor, which were higher in mice with high trait anxiety than in mice with low trait anxiety. In summary, inbred C57BL/6 mice display a remarkably high interindividual variability in their trait anxiety that predicts the behavioral and neuroendocrine response to an acute stressor, indicating that expression of extremely different coping strategies can develop also between genetically identical individuals.